Corruption in the revenue from tobacco in the viceroyalty of New Granada: Embezzlement in the principal administration of Santafe (1778-1810). - Torres Güiza, Johan Sebastián (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article attempts to study the phenomenon of corruption in the revenue from tobacco in the New Kingdom of Granada in the late 18th century, from files that revenue sub-delegate judges presented against some tobacconists of the principal administration of Santafé, for embezzlement and the scale of their accounts. Qualitative and quantitative documents from the National Archives (Colombia), such as records of «debt in favour» as a historical source for the study of corruption and its possible quantification, and the mechanisms used by the revenue to punish embezzlement and provide redress to the Royal Treasury. In conclusion, the article contributes to explaining how the absence of a fixed salary for the administrators of the revenue from tobacco led to corrupt practices which were understood and judged as embezzlement.